QUALITY EDUCATION IN JOURNALISM IN UZBEKISTAN (Journal of Science-Innovative Research in Uzbekistan, 2024)
the article talks about the proposals and their importance for bringing the system of training in the field of journalism to a new level in Uzbekistan. Also, the problems and issues of the current situation are considered.